2023
DOI: 10.1186/s13578-023-00996-7
|View full text |Cite
|
Sign up to set email alerts
|

SEPT2 crotonylation promotes metastasis and recurrence in hepatocellular carcinoma and is associated with poor survival

Abstract: Background Hepatocellular carcinoma (HCC) metastasis and recurrence lead to therapy failure, which are closely associated with the proteome. However, the role of post-translational modification (PTM) in HCC, especially for the recently discovered lysine crotonylation (Kcr), is elusive. Results We investigated the correlation between crotonylation and HCC in 100 tumor tissues and performed stable isotope labeling by amino acids and liquid chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Accumulating evidence has shown that proteins in human tumor tissues can be modi ed by crotonylation [22,23]. In several carcinoma types, including thyroid, esophagus, colon, pancreas, and lung, the global crotonylation was remarkably increased, while it was reduced in liver, stomach, and kidney carcinomas [24].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that proteins in human tumor tissues can be modi ed by crotonylation [22,23]. In several carcinoma types, including thyroid, esophagus, colon, pancreas, and lung, the global crotonylation was remarkably increased, while it was reduced in liver, stomach, and kidney carcinomas [24].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that crotonylation can modulate protein function in human tumor tissues. 30 , 31 Global crotonylation levels have been found to be significantly increased in various carcinoma types, including thyroid, esophagus, colon, pancreas, and lung, while reduced in liver, stomach, and kidney carcinomas. 32 These observations indicate that crotonylation may play diverse roles in cancer progression by influencing distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging evidence also highlights the positive relationship between novel acylation and HCC; it was documented that the Kcr of Septin 2 (SEPT2) promotes the invasion of HCC cells, with the SEPT2 in highly invasive HCC cells significantly hypercrotonylated; conversely, the K74 mutation of SEPT2 delayed its Kcr, leading to decreased GTPase activity of SEPT2 and impaired HCC metastasis in vitro and in vivo [ 142 ]. Previous research mentioned that mitochondrial transcription factor A (TFAM) downregulation in metastatic HCC induced Kma of mDia2 to promote its nuclear translocation and actin polymerization, thereby resulting in the high metastatic ability of HCC cells [ 143 ].…”
Section: Roles Of Novel Acylations In Tumor Metastasesmentioning
confidence: 99%